2010
DOI: 10.4314/njps.v21i1-2.53957
|View full text |Cite
|
Sign up to set email alerts
|

Influence of smoking on respiratory symptoms and lung function indices in sawmill workers in Benin city, Nigeria.

Abstract: The study was done to assess the influence of smoking on respiratory symptoms and respiratory function in sawmill workers in Benin City. 150 sawmill workers who were all males and aged between 18 and 50 years, and had been in continuous employment in sawmill factories for a minimum of one year were studied. They were selected by a two-stage random sampling process from sawmills in Benin City. These were compared to 150 age and sex matched controls in order to determine the effect of sawdust exposure on the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 12 publications
2
17
3
Order By: Relevance
“…In our study most of the workers had sawdust exposure of <5 years with a mean duration of exposure (years)= 7.59±5.89 years. These findings are consistent with the findings of Oluwatosin et al, Ugheoke et al 15,18 However contradictory observations were noted by Sakariya et al and Boskabady et al 1,16 This could be due to the unskilled workers employed in unorganized sector with frequent job changing tendency in present study.…”
Section: Discussionsupporting
confidence: 92%
“…In our study most of the workers had sawdust exposure of <5 years with a mean duration of exposure (years)= 7.59±5.89 years. These findings are consistent with the findings of Oluwatosin et al, Ugheoke et al 15,18 However contradictory observations were noted by Sakariya et al and Boskabady et al 1,16 This could be due to the unskilled workers employed in unorganized sector with frequent job changing tendency in present study.…”
Section: Discussionsupporting
confidence: 92%
“…occupational exposures in sawmill implied that workers in sawmills are at risk of ill health. In Nigeria, various studies have shown the role of occupational exposure to environmental pollutants in the incidence of respiratory diseases (3). Another example is the high levels of noise that have long been recognized by industrial safety technicians as unsafe to workers.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, along many years before, asthma was reported among brick kilns workers with variable prevalence that ranged generally between 6% and 14% in those studies : Myers et al, 1989;Friis et al,1999;Mustajbegovic et al, 2003;Mwaiselage et al, 2005;Ugheoke et al, 2006;Dehghan et al, 2009;and Singh et al, 2011). Monga et al, (2012), clarified that the increased prevalence of respiratory complaints like cough, phlegm, wheezing, breathlessness and asthma among brick kiln workers were due to exposure to respirable dust levels which exceed the respirable dust limit of 5.0 mg/m3 as given by OSHA and the Indian Union Ministry of Labour in absence of proper protective equipments causing serious health problems.…”
Section: Discussionmentioning
confidence: 98%